1985
DOI: 10.1083/jcb.100.2.435
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of fluorescent derivatives of cytochrome c in mitochondria.

Abstract: Motion of cytochrome c bound to giant (2-10-micron diam) mitochondria isolated from the waterbug Lethocerus indicus was examined using the technique of fluorescence recovery after photobleaching. Fluorescent cytochrome c was exchanged for native cytochrome c through partly damaged outer membrane. Recovery profiles were not statistically different when the fluorescence from iron-free cytochrome c or fluorescein-labeled cytochrome c was used and were essentially the same in the presence or absence of an uncouple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The functional relevance of these structural changes in cytochrome c is dependent upon the extent to which the protein can be considered to interact with components of the inner mitochondrial membrane other than its redox partners. Results from fluorescence photobleaching experiments at physiological ionic strength (Vanderkooi et al, 1985) showed that iron-free porphorin cytochrome c exists in two motional states at the inner membrane: one with a quite restricted lateral diffusion (D = ~10'10 cm2 s"1) and the other comprising an "immobile" pool at this site. On the other hand, Gupte and Hackenbrock (1988) report that, at physiological ionic strengths, cytochrome c is not immobilized to any significant extent at the inner membrane, and therefore, they assume a diffusion coefficient for the free protein in aqueous solution (~1 CT6 cm2 s'1).…”
Section: Methodsmentioning
confidence: 99%
“…The functional relevance of these structural changes in cytochrome c is dependent upon the extent to which the protein can be considered to interact with components of the inner mitochondrial membrane other than its redox partners. Results from fluorescence photobleaching experiments at physiological ionic strength (Vanderkooi et al, 1985) showed that iron-free porphorin cytochrome c exists in two motional states at the inner membrane: one with a quite restricted lateral diffusion (D = ~10'10 cm2 s"1) and the other comprising an "immobile" pool at this site. On the other hand, Gupte and Hackenbrock (1988) report that, at physiological ionic strengths, cytochrome c is not immobilized to any significant extent at the inner membrane, and therefore, they assume a diffusion coefficient for the free protein in aqueous solution (~1 CT6 cm2 s'1).…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence Recovery after Photobleaching. The fluorescence photobleaching apparatus and the method of data analysis have been previously described (Vanderkooi et al, 1985). FRAP measurements were performed on the prepared sample at 10, 15, 20, 24, 25, 30, and 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Although the components and mechanisms of the mitochondrial protein transport machinery are well understood 10 11 12 13 14 , knowledge about the movement of these proteins in the mitochondrial membrane is scarce. Research in this direction is currently limited to a recent investigation of a fluorescently labeled Tom40-associated subunit of the TOM complex, Tom7 by Fluorescence Recovery After Photobleaching (FRAP) 15 , a technique previously used for investigating protein diffusion in the mitochondrial matrix 16 17 18 19 . Tom7 was observed to have strongly heterogeneous diffusive properties: the majority of the protein population is freely diffusive, with a diffusion coefficient along the mitochondrial axis in the outer membrane of 0.7 μm 2 /s, whereas a minor sub-population (7%) is virtually immobile 15 .…”
mentioning
confidence: 99%